Performance and return to sport after anterior cruciate ligament reconstruction in X-Games skiers and snowboarders - Erickson, B. J.; Harris, J. D.; Fillingham, Y. A.; Cvetanovich, G. L.; Bhatia, S.; Bach Jr, B. R.; Bush-Joseph, C. A.; Cole, B. J. (Orthopaedic Journal of Sports Medicine, 2013)
Background: Skiing and snowboarding have become increasingly popular since the inception of the winter X-Games in 1997.